ACCOUNTING FOR THE DAIRY PRODUCTS INDUSTRY. - Cooper, Robert S. (The Accounting Review, 1945)
Abstract The article focuses on accounting for the dairy products industry. Twenty-five years ago the milk from a cow would arrive at the consumer's door step about twelve hours after milking time. Today this interval is much longer. The entrepreneur plays a much larger part in the dairy business than formerly. In fact, the processing distributor is almost a monopolist in the large metropolitan areas. It should be stated that accounting technique in the dairy industry has kept pace with technological advances and the transition from the horse and wagon to the paneled milk truck. In the heyday of the farmer-distributor no complicated accounting problems were encountered. Monthly receipts could be set off against comparatively few expense items. The farmer did not think in terms of depreciation, reserves for bad debts, or obsolescence. It can be truthfully said about accounting for the dairy industry that although the hours are long and the toil sometimes irksome, there is never a dull moment. Accounting for depreciation of equipment, machinery, and trucks likewise is a topic about which a separate article could be written.